Exogenous melatonin enhances the tolerance of tiger nut (Cyperus esculentus L.) via DNA damage repair pathway under heavy metal stress (Cd2+) at the sprout stage - Li, Caihua; Liu, Jiayao; Wei, Zunmiao; Cheng, Yan; Shen, Zihao; Xin, Zhuo; Huang, Yudi; Wang, Hongda; Li, Yuhuan; Mu, Zhongsheng; Zhang, Qi (Ecotoxicology and environmental safety, 2023)
Heavy metal (HM) stress is a non-negligible abiotic stress that seriously restricts crop yield and quality, while the sprout stage is the most sensitive to stress and directly impacts the growth and development of the later stage. Melatonin (N-acetyl-5-methoxytryptamine), as an exogenous additive, enhances stress resistance due to its ability to oxidize and reduce. However, few reports on exogenous melatonin to tiger nuts under HM stress have explored whether exogenous melatonin enhances plants' resistance to heavy metals. Here, “Jisha 2″ was used as material, with a stress concentration of 5 mg/L and 100 μmol/L of CdCl2 to explore whether exogenous melatonin enhances plant resistance and molecular mechanism. The result revealed that stress limits growth, while melatonin alleviated the sprout damage under stress from the phenotypes. Moreover, stress-enhanced reactive oxygen species (ROS) accumulation and membrane lipid peroxidation, while melatonin-increased ROS reduce damage via the analysis of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) and malondialdehyde (MDA) content, hydrogen peroxide (H2O2), superoxide anion (O2-), and Electrolyte leakage (El). Further results indicated that HM leads to DNA damage while exogenous melatonin will repair the damage by analyzing random amplified polymorphic DNA (RAPD), DNA cross-linking, 8-hydroxy-20-deoxyguanine level, and relative density of apurinic sites. Furthermore, gene expression in the DNA-repaired pathway exhibited similar results. These results applied that exogenous melatonin released the hurt caused by HM stress, with DNA repair and ROS balance serving as candidate pathways. This study elucidated the mechanism of melatonin's influence and provided theoretical insights into its application in tiger nuts. [Display omitted] •Exogenous melatonin enhanced the tiger nut (Cyperus esculentus L.) tolerance via phenotype and physiology.•ROS accumulation and DNA damage are two pathways for tiger nuts under heavy metal stress.•Exogenous melatonin balanced ROS accumulation and repaired DNA damage to alleviate damage.